Analisa Perbandingan Trend Laju Inflasi di Indonesia dan Malaysia - Mahrani Rangkuty, Dewi; Lola Irmayunda; Jumadil Saputra (Journal of Islamic Economics and Finance, 2024)
Economic growth serves as a crucial indicator in evaluating the well-being of a country. This study analyzes the economic growth of Indonesia and Malaysia from 2017 to 2023, taking into account the impact of inflation on the achievement of economic goals. The research employs a qualitative descriptive method with a literature review through literature analysis. The results reveal that the economic structures of both countries share similarities, particularly in the sectors of agriculture, forestry, and mining. Indonesia's economic growth tends to be higher than Malaysia's during this period, despite experiencing fluctuations. The sectoral contributions to Gross Domestic Product (GDP) indicate the dominance of the industrial sector in both economies. The significance of economic growth is also considered by examining the inflation rates. Indonesia consistently experiences higher inflation rates than Malaysia, potentially indicating challenges in maintaining macroeconomic stability. Higher inflation rates in Indonesia can impact the well-being of the population and create instability in the prices of goods and services. This research provides insights into the dynamics of economic growth and inflation in Indonesia and Malaysia, as well as their implications for achieving economic development goals. The success of a country in attaining sustainable economic growth requires special attention to factors such as economic structure, sectoral contributions, and inflation stability.